2022
DOI: 10.3389/fpubh.2022.957619
|View full text |Cite
|
Sign up to set email alerts
|

Effects of childcare disagreement with children, social support, and health status on unmet healthcare-seeking behavior among the migrant older with children to Jinan, China

Abstract: Due to the acceleration of China's urbanization, the number of migrant older with children (MOC) continued to increase. This study aimed to clarify the effects of childcare disagreement with children, social support, and health status on unmet healthcare-seeking behavior among the MOC to Jinan, China. A cross-sectional study included 656 MOC (36.3% men and 63.7% women) using multi-stage cluster random sampling in Jinan, China. Childcare disagreement was evaluated by the differences between parents and grandpar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…The epidemiological data published by Zhang et al (9) shows that the prevalence of falls among urban older people in China is lower than that among rural people (15.0 vs 17.0%), while our data showed that the prevalence of falls among urban and rural older people was similar (21.8 vs 21.2%). Another study showed that in recent years, with the development of urbanization in China, the number of older people in urban areas has been continuously increasing (14), which may be the reason for the increase in falls among the older population compared to before (9). A survey showed that in 2018 the prevalence of falls among adults aged 65 years and older in the U.S. in the past year was 27.5% (15), which suggests that the prevalence of falls among older adults in China is lower than that in the U.S. but that the absolute number of falls among older adults in China is greater.…”
Section: Discussionmentioning
confidence: 99%
“…The epidemiological data published by Zhang et al (9) shows that the prevalence of falls among urban older people in China is lower than that among rural people (15.0 vs 17.0%), while our data showed that the prevalence of falls among urban and rural older people was similar (21.8 vs 21.2%). Another study showed that in recent years, with the development of urbanization in China, the number of older people in urban areas has been continuously increasing (14), which may be the reason for the increase in falls among the older population compared to before (9). A survey showed that in 2018 the prevalence of falls among adults aged 65 years and older in the U.S. in the past year was 27.5% (15), which suggests that the prevalence of falls among older adults in China is lower than that in the U.S. but that the absolute number of falls among older adults in China is greater.…”
Section: Discussionmentioning
confidence: 99%
“…Their new city's social atmosphere might not be welcoming for them and may result in various prejudices for their livelihood stability. Such an unfavourable physical and social environment puts migrant's health at risk and increases their disease susceptibility (Hong et al, 2006;Shi et al, 2022). The most evident challenges to their access to healthcare are linguistic, cultural and financial constraints.…”
Section: Introductionmentioning
confidence: 99%
“…Gender disparities in healthcare access and mortality rates can also be observed in Shumen. Societal factors may influence healthcare-seeking behaviors among elderly men and women differently, affecting their overall health outcomes (Shi, Zong, Lu, Li & Kong, 2022). These disparities warrant attention in healthcare policy and programming.…”
mentioning
confidence: 99%